2007
DOI: 10.1177/1468796807080230
|View full text |Cite
|
Sign up to set email alerts
|

Guest editorial

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(47 citation statements)
references
References 9 publications
(8 reference statements)
1
41
0
5
Order By: Relevance
“…Regarding the associations with migration background, the finding that students with a migration background had higher odds of choosing the general educational track is in line with previous research (e.g., Relikowski, Schneider, & Blossfeld, 2009;Rosenbaum & Rochford, 2008). In the literature, this effect has been explained by the fact that migrants are a positively selected group in terms of their work ethic and ambition (socalled Immigrant Optimism; e.g., Heath & Brinbaum, 2007). Furthermore, some authors have argued that migrants overestimate the probability that they will master higher educational tracks (e.g., Relikowski et al, 2009).…”
Section: Which Factors Are Associated With Educational Track Choices?supporting
confidence: 88%
“…Regarding the associations with migration background, the finding that students with a migration background had higher odds of choosing the general educational track is in line with previous research (e.g., Relikowski, Schneider, & Blossfeld, 2009;Rosenbaum & Rochford, 2008). In the literature, this effect has been explained by the fact that migrants are a positively selected group in terms of their work ethic and ambition (socalled Immigrant Optimism; e.g., Heath & Brinbaum, 2007). Furthermore, some authors have argued that migrants overestimate the probability that they will master higher educational tracks (e.g., Relikowski et al, 2009).…”
Section: Which Factors Are Associated With Educational Track Choices?supporting
confidence: 88%
“…Second, the 'information bias' approach argues that migrant families and their children tend to overestimate their real schooling and labour market chances because of their lack of information on how these institutions operate, for example via cultural or linguistic barriers (Kao and Tienda 1998;Lareau 2015). Third, the 'blocked opportunities' thesis suggests that minority pupils anticipate ethnic discrimination in their future school-to-work transition, which brings them to aim high in the educational system to overcome potential discrimination in the labour market (Heath and Brinbaum 2007;Jackson, Jonsson, and Rudolphi 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Shavit, Yaish, and Bar-haim (2007) explain this link by mechanisms related to economic and cultural resources, the influence of other family members, track placement, and incentives to make more ambitious educational decisions. Second, many studies in Europe and the United States have found that foreignborn children and racial minorities have lesser educational outcomes (Heath and Brinbaum 2007;Hirschman 2001;Riphahn 2003). Odds by language and religion in Figure 2 illustrate that many groups with an immigrant background have a much lower likelihood of obtaining a post-secondary level than others.…”
Section: Inequality In Labor Force Participation and Educationmentioning
confidence: 96%